Numb is required for optimal contraction of skeletal muscle. Issue 1 (9th January 2022) - De Gasperi, Rita; Mo, Chenglin; Azulai, Daniella; Wang, Zhiying; Harlow, Lauren M.; Du, Yating; Graham, Zachary; Pan, Jiangping; Liu, Xin‐hua; Guo, Lei; Zhang, Bin; Ko, Fred; et al.
Abstract: Background: The role of Numb, a protein that is important for cell fate and development and that, in human muscle, is expressed at reduced levels with advanced age, was investigated; adult mice skeletal muscle and its localization and function within myofibres were determined. Methods: Numb expression was evaluated by western blot. Numb localization was determined by confocal microscopy. The effects of conditional knock out (cKO) of Numb and the closely related gene Numb‐like in skeletal muscle fibres were evaluated by in situ physiology, transmission and focused ion beam scanning electron microscopy, three‐dimensional reconstruction of mitochondria, lipidomics, and bulk RNA sequencing. Additional studies using primary mouse myotubes investigated the effects of Numb knockdown on cell fusion, mitochondrial function, and calcium transients. Results: Numb protein expression was reduced by ~70% ( P  < 0.01) at 24 as compared with 3 months of age in gastrocnemius and tibialis anterior muscle. Numb was localized within muscle fibres as bands traversing fibres at regularly spaced intervals in close proximity to dihydropyridine receptors. The cKO of Numb and Numb‐like reduced specific tetanic force by 36% ( P  < 0.01), altered mitochondrial spatial relationships to sarcomeric structures, increased Z‐line spacing by 30% ( P  < 0.0001), perturbed sarcoplasmic reticulum organization and reduced mitochondrial volume by over 80% ( P  < 0.01). Only six genes were differentially expressed in cKO mice: Itga4, Sema7a, Irgm2, Vezf1, Mib1, and Tmem132a . Several lipid mediators derived from polyunsaturated fatty acids through lipoxygenases were up‐regulated in Numb cKO skeletal muscle: 12‐HEPE was increased by ~250% ( P  < 0.05) and 17, 18‐EpETE by ~240% ( P  < 0.05). In mouse primary myotubes, Numb knockdown reduced cell fusion (~20%, P  < 0.01) and delayed the caffeine‐induced rise in cytosolic calcium concentrations by more than 100% ( P  < 0.01). Conclusions: These findings implicate Numb as a critical factor in skeletal muscle structure and function and suggest that Numb is critical for calcium release. We therefore speculate that Numb plays critical roles in excitation–contraction coupling, one of the putative targets of aged skeletal muscles. These findings provide new insights into the molecular underpinnings of the loss of muscle function observed with sarcopenia.